REVEALING THE ACCOUNTABILITY TRANSFORMATION OF COMMUNAL BASED MICROFINANCE INSTITUTIONS IN INDONESIA - Fauzi N.; Irianto G.; Hariadi B.; Roekhudin (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research is aimed at revealing accountability practices at the oldest Communal Based Microfinance Institution in Indonesia, Lumbung Pitih Nagari. Lumbung Pitih Nagari is a traditional microfinance institution owned by the nagari community (traditional village) and transformed into a formal financial institution (rural credit banks and cooperatives). This research was carried out during 2017-2018 on several research sites spread across three districts / cities in Indonesia's West Sumatra province. Data collection is done by in-depth interviews, observation and documentation. Research informants were determined in advance for several key informants and the rest followed the snowball sampling pattern. Data analysis was carried out following 12 stages of sequential development methods introduced by Spradley in Realist ethnographic research. This study found a change in direction and form of accountability from the social base to rule base on the Lumbung pitih nagari which turned into rural credit bank. While the Lumbung pitih nagari turned into cooperatives, there was also a change in direction and form of accountability, although it was not significant, as happened in the Lumbung Pitih Nagari which turned into a rural credit bank. In the final section, this study found changes in the Lumbung Pitih Nagari to become a rural credit bank or cooperatives make the Lumbung Pitih Nagari uprooted from its roots as a communal nagari-based microfinance institution that should contribute to the development of economic, social, religious and cultural aspects of the Nagari community